Are early first trimester weights valid proxies for preconception weight?. Issue 1 (December 2016) - Krukowski, Rebecca; West, Delia; DiCarlo, Marisha; Shankar, Kartik; Cleves, Mario; Saylors, Marie; Andres, Aline
Abstract Background An accurate estimate of preconception weight is necessary for providing a gestational weight gain range based on the Institute of Medicine's guidelines; however, an accurate and proximal preconception weight is not available for most women. We examined the validity of first trimester weights for estimating preconception body mass index category. Methods Under identical measurement conditions, preconception weight and two first trimester weights (i.e., 4–10 and 12 weeks gestation) were obtained (n  = 43). Results The 4–10 week and the 12 week weight correctly classified 95 and 91% women, respectively. Mean weight changes were relatively small overall (M  = 0.74 ± 1.99 kg at 4–10 weeks andM  = 1.02 ± 2.46 at 12 weeks). There was a significant difference in mean weight gain by body mass index category at 4–10 weeks (−0.09 ± 1.86 kg for normal weight participants vs. 1.61 + 1.76 kg for overweight/obese participants, p  = 0.01), but not at 12 weeks (0.53 ± 2.29 kg for normal weight participants vs. 1.54 ± 2.58 kg for overweight/obese participants). Conclusions Assigning gestational weight gain guidelines based on an early first trimester weight resulted in 5–9% of women being misclassified depending on the gestational week the weight was obtained. Thus, most women are correctly classified based on a first trimester weight, particularly an early first trimester weight, although it is possible that modeling strategies could be developed to further improve estimates of preconception body mass index category. Trial registration Clinicaltrials.gov #NCT01131117, registered May 25, 2010.